Classical Chinese Gardens: Landscapes for Self-Cultivation - Donia Zhang (Journal of Contemporary Urban Affairs, 2018)
This paper examines the design philosophy of classical Suzhou gardens in China, with regards to their natural and architectural elements on the moral education of the inhabitants. Through studying the metaphorical connotations of garden elements, the author reflects on their propositions for contemporary environmental ethics, aesthetic appreciation, and moral education. As such, the article is structured around three themes: classical Chinese gardens cultivating environmental ethics, classical Chinese gardens cultivating an appreciation of aesthetics, and classical Chinese gardens cultivating moral characters. The essay finally suggests that classical Chinese gardens are landscapes for self-cultivation.